Innovative Approaches to Teaching Grammar - Ahmedova Nodira Djavadullaevna (Bright Mind Publishing, 2025)
This article explores innovative approaches for teaching grammar to young learners. Traditional methods, such as rote memorization and explicit rules, are compared with more engaging strategies like inductive learning, games, and storytelling. The role of technology and interactive tools in enhancing grammar instruction is also discussed. These methods are designed to make grammar learning fun, meaningful, and effective for children, focusing on practical use rather than mere rule memorization.
Keywords: Grammar teaching, young learners, inductive learning, games, storytelling, interactive tools, digital resources, language acquisition.